Emotional-expressive vocabulary in poetical speech (on the material of the poetry by Lina Kostenko) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The role of emotional-expressive vocabulary in poetical speech is determined. The individual-author’s usage of inherent and adherent emotional lexicon as a basis of expressivity is defined. The author reasons that emotional-expressive vocabulary gets extra nuances of meaning in the poetical context.
Keywords: emotionality; expressivity; emotional-expressive vocabulary